Surface Science and Heterogeneous Catalysis - G.A. Somorjai (CHIMIA)
Surface Science has been increasingly utilized in recent years to explore the molecular details of heterogeneous catalytic processes. A large number of techniques have been developed that determine the atomic surface structure, the composition, and oxidation states in the surface monolayer. Correlations of studies of catalytic reaction rates and product distributions with atomic scale surface properties revealed many important ingredients of surface reactivity. The structure of the catalyst surface markely influences the surface chemical bonds of adsorbed molecules. Additives which are often electron donors (alkali metals) or electron acceptors (halogens) change the oxidation state of surface atoms, block sites, or change the surface structure. Their effects are demonstrated in this paper through several examples. The building of new «high technology» catalysts, using the principles of catalyst behavior uncovered by surface science, appears possible.